Internal Genital Organ-preserving Radical Cystectomy: A Case Report - WIDIA, FINA; SITUMORANG, GERHARD R; HAMID, AGUS RIZAL A.H; MOCHTAR, CHAIDIR A (Indonesian Journal of Cancer, 2016)
ABSTRACTAdenocarcinoma of the bladder is usually managed by radical cystectomy. However, recent literature shows that internal genital organ-preserving radical cystectomy is feasible in selected cases in order to get a better impact on patientâs psychology, sexuality and potential fertility. Here, we report a 32-year-old woman with adenocarcinoma of the bladder who was managed with internal genital organ-preserving radical cystectomy. The patient was never had any child and the radiologic examination (MRI) showed no involvement of internal genitalia organ. This procedure aims to maintain fertility potential of the patient. Intraoperatively, no adhesion was found between the tumor and internal genitalia organ. The internal genitalia organ was successfully preserved during the radical cystectomy.Â ABSTRAKTata laksana adenokarsinoma kandung kemih umumnya berupa sistektomi radikal. Akan tetapi, penelitian terbaru menunjukkan bahwa preservasi organ internal genitalia dapat diterapkan pada kasus-kasus tertentu dengan tujuan untuk mempertahankan potensi seksual dan fertilitas pasien. Saat ini kami melaporkan seorang perempuan berusia 32 tahun dengan adenokarsinoma kandung kemih yang menjalani sistektomi radikal dengan tetap mempertahankan organ genitalia interna. Pasien merupakan nulipara dan pada pemeriksaan radiologi MRI tidak didapatkan infiltrasi tumor pada organ genitalia interna. Prosedur operasi dilakukan dengan tujuan mempertahankan potensi fertilitas. Intraoperatif, tidak didapatkan perlengketan antara tumor dan organ genitalia interna. Organ genitalia interna berhasil dipreservasi selama prosedur sistektomi radikal.